THE ANALYSIS OF THE PROVERBS OF ENGLISH AND UZBEK (The Role of Exact Sciences in the Era of Modern Development, 2025)
This thesis is devoted to the analysis of one of the large groups of proverbs that form the main structure of English and Uzbek paremiology. Proverbs related to hard work and laziness are taken as examples of two languages and are analyzed in different semantic aspects.